Human resources in China's disease prevention and control institu-tions - allocation equity in 2014 and 2019 - Tian-tian ZHANG; Wen-qiang YIN; Cui-xiang MENG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine the equity in human resources allocation in centers for disease prevention and control (CDCs) and to provide evidences for optimizing resource allocation. Methods The data on human resources among CDCs in all administrative regions across China in 2014 and 2019 were collected from China's Statistical Yearbook of Health and Family Planning - 2015 and China's Statistical Yearbook of Health - 2020. Then, health resource agglomeration degree (HRAD) was used to evaluate the equity in human resources allocation according to population and geographical area. Results The total number of personnel in CDCs across China decreased by 2.51% from 192 397 in 2014 to 187 564 in 2019. The number of CDCs' personnel per 10 000 population also showed a shrinking trend at all provincial levels and the number for most provincial level regions did not meet the national standard. In 2019, the proportions of CDC personnel at young age (< 35 years) and middle-aged (35 - 54 years) decreased by 3.8% and 2.4% compared with those in 2014, but the proportion of elderly personnel (≥ 55 years) increased by 6.0% contrasting to that in 2014. The number of personnel with high school/technical secondary school education or below in all CDCs in China decreased from 28.8% in 2014 to 19.4% in 2019, while the number of those with junior college education or above increased from 71.1% in 2014 to 80.6% in 2019. The results of analysis on the equity in human resources allocation showed that the spatial distribution of human resource was unbalanced. The geographical region-specific HRAD index was the highest (indicating a better equity in human resources allocation) for eastern region, followed by that for central and western region; while, the population distribution-specific HRAD index was higher for western region than that for central and eastern region. Conclusion Insufficient total number, serious turnover and unbalanced allocation are main problems in health resources allocation for CDCs in China and the situation needs to be improved for CDCs' capability construction in China.